Review of the Fatwa of the National Sharia Council (DSN-MUI) on Financing the Hajj Management of Sharia Financial Institutions at BMT NU - Umaroh, Ely; fajar, fajar (Universitas Trunojoyo Madura, 2024)
The hajj bailout in Indonesia raises pros and cons because every product must have a positive and negative impact. This study aims to reveal how the mechanism for the hajj bailout fund is implemented in BMT NU.The research method used is qualitative research, the type of field research (field research) is descriptive analysis, and the subjects include employees of BMT NU Ngasem – East Java. Data collection techniques through observation and interviews. The data analysis method is carried out inductively, namely analyzing data whose process is direct from fact to theory which makes the author go into the field to study, analyze, and draw conclusions then that is the result of the research.The results of the study show that the hajj bailout products have met sharia principles. The implementation of the hajj bailout uses two contracts, qard and ijarah. The qard contract is used as an agreement in providing hajj bailout funds to customers, and the ijarah contract is used when BMT NU takes care of hajj registration online through the Integrated Hajj Computerization System (Siskohat).